Marginal intra-industry trade and adjustment costs in labour market - Nuno Carlos Leit\~ao; Bogdan Dima; Dima Cristea Stefana (Fondazione Eni Enrico Mattei (FEEM), 2013)
The objective of this study is to provide some empirical evidences on the existence of labor market adjustments according to smooth adjustment hypothesis (SAH) under the impact of intra-industry trade (IIT) considering the Portuguese case over a time span between 1995 and 2006. The main methodological issue of this study consists in showing that it is preferable to use the GMM-System approach with orthogonal transformation of data. The key outcome consists in highlighting a negative linkage between marginal intra-industry trade and the amplitude of employment changes for this particular market. In addition, we find a negative correlation between changes of employment and changes in domestic consumption. Moreover, the relationship between growth of productivity and market structure is according to smooth adjustment hypothesis.
Keywords: F12; C33; 330; Intra-Industry Trade; Adjustment Costs; Portugal; Labour Market